Individualisation of personal space in hospital environment. (1st January 2014) - Dovjak, Mateja; Shukuya, Masanori; Krainer, Aleš
The purpose of the paper is to test a Low Exergy heating and cooling system (LowEx system) that enables the creation of healing and comfort conditions for individual user with minimal possible energy use. The LowEx system was tested in a model room for burn patient and compared with the conventional one. Thermal comfort conditions were simulated for three individual users (burn patient, healthcare worker and visitor) energy use was measured. In a simulation, users were exposed to the required conditions for burn patient created with both systems. The LowEx system creates optimal conditions for burn patient with lower human body exergy consumption (hbExC) rate valid for thermoregulation, minimal evaporation, radiation and convection. For healthcare worker and visitor, the LowEx system creates individual thermal comfort zones. For the LowEx system, the measured energy use for heating was 11–27% lower and for cooling 32–73% lower than for the conventional system.